«Matisos culinaris». La importància de la gastronomia en la construcció de Cartes d'Itàlia (1955) de Josep Pla. - PORTILLO DE BARRIO, DAVID (Scripta)
This article studies the presence of gastronomy in Cartes d'Itàlia (1955) by Josep Pla. Based on the possible incentives that prompted Pla to write a second writing based on Italy's cuisine, the content of this is briefly described, as well as the role of regional cuisine when defining a territory. Next, the various rewriting processes to which the article was subjected, until it was integrated into Cartes d'Itàlia, are analysed. Finally, thanks to the literary reworking, changing aspects of Pla's thinking about the gastronomy of Italy are highlighted. The annex incorporates the transcription of all the variants.